(untitled) (Research, Society and Development, 2024)
Emotional regulation is the use of conscious or unconscious processes that alter the nature, intensity, or duration of emotions. Dysfunctional emotions are a core part of the symptomatology of mental disorders. They are a major source of psychological distress and the main reason for seeking help in mental health. Emotional regulation is an integral part of different approaches in psychotherapy, and greater knowledge about the neural processes involved can enable the improvement of treatment strategies. The aim of this article is to present a narrative review of the literature that addresses advances in understanding the neural bases involved in emotion regulation strategies. Emotions result from the activation of several neural networks in a joint and integrated work. This network includes areas that play a prominent role, such as the thalamus, amygdala, insula, ventral striatum, medial prefrontal cortex, orbitofrontal cortex, somatosensory cortex, and anterior cingulate. These areas are also involved in emotional regulation either as a target or as agents of regulation. Reappraisal, which is the most studied strategy, in addition to decreasing amygdala activity, recruits prefrontal and parietal regions involved in non-affective cognitive control processes, such as response inhibition, task switching, and working memory. Research in this field with the new approaches of identifying distinct circuits by optogenetic and chemogenetic methods is quite promising. Deepening knowledge of these processes has the potential to provide a cross-theoretical and transdiagnostic point of convergence in psychotherapy.